Potencial biotecnológico de fungos de origem marinha: produção de enzimas ligninolíticas e avaliação da toxicidade - Yoshida, Aline Mayumi da Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Marine-derived fungi represent a group of unexplored organisms from the ecological and biotechnological points of view, but with advantages for applications in environments or saline processes. The laccase enzyme belongs to the group of oxidades, which can act in the degradation of various environmental pollutants such as textile dyes and polycyclic aromatic hydrocarbons (PAHs). This study aimed to select the best ligninolytic fungus of marine origin among 115 isolated and optimize the laccase production by evaluating different factors with experimental design. Additionally, the enzymatic production in the presence of three textile dyes (Brilliant Blue Remazol R - RBBR, Reactive Black 5 and Black Sulphurous) and HPA pyrene, as well as the ability to detoxify pollutants and decrease colors by the selected fungus were evaluated. The quantification of the enzyme laccase was made by spectrophotometry using ABTS as substrate and resulted in the selection of the isolate LAMAI 659. The optimization of culture conditions for laccase production by the selected fungus was performed using sequential statistical technique Plackett & Burman (P&B). In the initial screening, the fungus showed 68.89 U/L of laccase production. The results of the first P&B (with 10 variables) showed that maximum enzyme production (82.25 U/L) was 19% higher than in a non-optimized medium, with positive but not significant effects for the following variables: yeast extract, pH, wheat bran, glucose, temperature, peptone and malt extract. In the second P&B, with 8 variables, there is even greater increase in enzyme production values, reaching 415.89 U/L. However, statistically significant effect again were not observed. The variables temperature, yeast extract, inoculum number and wheat bran presented positive effect. In the third P&B were also used 8 variables, with the addition of guaiacol and alcohol veratryl as inducers. The production of laccase was 970.68 U/L...

Fungos marinhos representam um grupo de organismos pouco explorado dos pontos de vista ecológico e biotecnológico, mas com grande vantagem para aplicações em ambientes ou processos salinos. A enzima lacase pertence ao grupo das oxidades, que podem atuar na degradação de diversos poluentes ambientais, como corantes têxteis e hidrocarbonetos policíclicos aromáticos (HPAs). O presente trabalho teve como objetivo principal selecionar o melhor fungo ligninolítico de origem marinha dentre 115 isolados e otimizar a produção de lacase avaliando diferentes fatores por desenho experimental. Em adição, a produção enzimática na presença de três corantes têxteis (Azul Brilhante de Remazol R - RBBR, Preto Reativo 5 e Preto Sulfuroso) e do HPA pireno, bem como a capacidade de detoxificação dos poluentes e descoloração dos corantes pelo fungo selecionado foram avaliadas. A quantificação da enzima lacase foi feita por espectrofotometria utilizando ABTS como substrato e resultou na seleção do isolado LAMAI 659. A etapa de otimização dos parâmetros de cultivo para produção de lacase pelo fungo selecionado foi realizada pela técnica estatística sequencial de Plackett & Burman (P&B). Na triagem inicial, o fungo apresentou produção de 68,89 U/L de lacase. Os resultados do primeiro P&B, com 10 variáveis, mostraram que a máxima produção da enzima (82,25 U/L) foi 19% maior do que em meio não-otimizado, com efeito positivo porém não significativo das seguintes variáveis: extrato de levedura, pH, farelo de trigo, glicose, temperatura, peptona e extrato de malte. No segundo P&B, com 8 variáveis, observou-se incremento ainda maior nos valores de produção da enzima, atingindo 415,89 U/L. Porém, novamente não foram evidenciados efeitos estatisticamente...
Keywords: Biotecnologia; Enzimas de fungos; Fungos marinhos; Toxicidade - Testes